2017
DOI: 10.1186/s12938-017-0406-z
|View full text |Cite
|
Sign up to set email alerts
|

Paroxysmal atrial fibrillation recognition based on multi-scale wavelet α-entropy

Abstract: BackgroundThis study proposed an effective method based on the wavelet multi-scale α-entropy features of heart rate variability (HRV) for the recognition of paroxysmal atrial fibrillation (PAF). This new algorithm combines wavelet decomposition and non-linear analysis methods. The PAF signal, the signal distant from PAF, and the normal sinus signals can be identified and distinguished by extracting the characteristic parameters from HRV signals and analyzing their quantification indexes. The original ECG signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Dozens of features are related to HRV, and different modes of feature training cause differences in model performance. In [ 42 , 43 ], 5 min ECG signals were used for model training. The short ECG sequence contained limited information.…”
Section: Discussionmentioning
confidence: 99%
“…Dozens of features are related to HRV, and different modes of feature training cause differences in model performance. In [ 42 , 43 ], 5 min ECG signals were used for model training. The short ECG sequence contained limited information.…”
Section: Discussionmentioning
confidence: 99%
“…Machine-learning methods for PAF detection use retrospective analysis of freely available clinical ECG recordings or clinical databases. These are often based on detection and classification of atrial premature beats and other ECG abnormalities (Thong et al, 2004), or from interval analysis of atrial or ventricular depolarisations (Ghodrati et al, 2008;Mohebbi and Ghassemian, 2012;Xin and Zhao, 2017;Aronis et al, 2018), with specificity and sensitivity ranging between 71-93% and 85-96%, respectively, but requiring recording periods up to 30 min. However, convolutional neural networks achieve accuracy of detection in the range 75-95% using shorter recording periods of detection (Hsieh et al, 2020;Nurmaini et al, 2020).…”
Section: Methods Of Atrial Fibrillation Detectionmentioning
confidence: 99%
“…Over the past years, there has been an exponential interest in using various big data sources to further improve the AF risk prediction beyond the traditional AF risk factors (23,24). Specifically, multiple studies have employed AI-enabled algorithms to evaluate new-onset AF prediction by leveraging various big data modalities including the clinical data, ECGs, EHRs, and wearable devices (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42). Some of these studies showed that AI-enabled AF prediction models performed similar to or better than established traditional AF prediction models (25,(27)(28)(29)(30).…”
Section: Leveraging Big Data For Prediction Of New-onset Atrial Fibri...mentioning
confidence: 99%